Efficacy of Different Treatment Protocols in the Management of Malassezia Infected Dogs - Dharmalingam, Selvi; Appaiah, Kshama Manepanda; Thimmaiah, Ramesh Poojary; Isloor, Shrikrishna; Veeranna, Mahesh; Rao, Suguna (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Dogs presented to outpatient medicine unit, Veterinary College, Bengaluru, with clinical signs suggestive of Malassezia dermatitis were screened by cytological examination and these dogs comprised the study group. The present study was aimed to study the effectiveness of different treatment protocols such as conventional itraconazole, itraconazole pulse therapy and topical luliconazole therapy in Malassezia dermatitis in dogs. Dogs with clinical signs indicative of Malassezia dermatitis such as rancid odor, erythema, greasiness, hyperkeratinisation, hyperpigmentation and lichenification were subjected to cytological examination. Upon cytological examination, 24 dogs that were found positive for Malassezia spp were divided into three groups of eight dogs each. Skin swabs from these 24 dogs were cultured on Modified Dixon’s Agar (MDA) for the isolation of Malassezia spp. Treatment was done with lipophilic triazole antifungal, Itraconazole @5 mg/kg b. wt. sid, po for 21 days for group I and itraconazole @5mg/kg b wt po sid, two days in a week for three consecutive weeks for group II and topical imidazole antifungal luliconazole, for 21 days for group III. All the twenty four dogs were treated with systemic broad spectrum anti-bacterial cefadroxil @22 mg/kg b. wt. twice daily for 14 days and antihistamine, hydroxyzine @ 0.5 mg/kg bwt twice daily for 5 days with supportive care. The study proved that topical luliconazole and itraconazole pulse therapy are more effective clinically than conventional itraconazole on 21 day treatment regimen.